Penerapan Model Pembelajaran Teams Games Tournament (TGT) Pada Siswa Kelas IV SDN Dukuh Kupang V Surabaya - Tiara Dyah Ayu Prameswari; Anna Roosyanti; Erlin Kartikasari (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The learning model is a frame of the application of approaches, methods and techniques in learning that will be carried out by the teacher. The purpose of this study was to determine teacher activity, student activity, student responses, and student learning outcomes in the application of the Teams Games Tournament (TGT) learning model. This type of research is a descriptive qualitative research. The results of the teacher activity research at the first meeting showed good criteria with a percentage of 85.71% while at the second meeting the criteria were very good with a percentage of 91.07%. Student activity at the first meeting was good with a percentage of 70.83%, while the second meeting was very good with a percentage of 93.75%. The value of the student response questionnaire is classified as very good with a percentage of 89%, while classical student learning outcomes are classified as very good with a percentage of 83.33%. The conclusions show that the Teams Games Tournament (TGT) model is very effective and feasible to be used as a learning model in facilitating teachers and students when participating in the learning process of Natural Resources (SDA) materials.